Maxión S.A. - Fossati Figueiredo, Kleber (1995)
Maxion S.A. is a company that has been operating in Brazil since 1962, specialized in the production of agricultural machinery and engines, products in which it has a market share of 40% and 25% respectively. It is in the group of well-positioned manufacturers, with its turnover of 40% in the foreign market in 1989. However, the increase in agricultural productivity led to a reduction in the demand for agricultural machinery. Following this unfavorable scenario, the company made the strategic decision to transform its production process into a competitive factor through the implementation of the Just-in-Time (JIT) system. The present case starts with the background of the JIT system, then the procedures adopted by the company are described, from the training on the meaning of the system to the development of suppliers. Finally, the results before and after the first stage of implementation are given along with quantitative indicators and qualitative considerations regarding the evaluation of the experience.